HyBryte™ use in early-stage cutaneous T-cell lymphoma - Poligone, Brian; Alexander-Savino, Carolina V.; Kim, Ellen J.; Mangold, Aaron R.; Desimone, Jennifer; Wong, Henry K.; Rumage, Adam T.; Donini, Oreola; Haulenbeek, Andrea; Schaber, Christopher J.; Straube, Richard; Pullion, Christopher; et al. (Frontiers in Drug Discovery, 2023)
Cutaneous T-cell lymphoma (CTCL) is a rare type of non-Hodgkin lymphoma of the skin, where at later stages skin-homing malignant T-cells affect lymph nodes, blood, and visceral organs. Even though early CTCL does not affect survival, it can progress to more advanced stages of disease and have a significant effect on the quality of life of patients. Although expectant management is a treatment consideration in early disease stages, most patients cycle through different skindirected therapies throughout their lifetime. It can become a challenge to manage the serious and accumulating risk of side effects of these therapies, including various skin cancers and skin damage. Adverse effects from topical therapies limit their long-term utility. Thus, there is an unmet need for well-characterized therapies that have a rapid onset of action and minimal longterm/cumulative side effect profile. Most recently, the results of a Phase 3 study of topical HyBryte TM as a potential treatment for CTCL demonstrated its efficacy and safety profile. This article summarizes what is known about HyBryte™, focuses on its mechanism of action, and highlights its effectiveness, safety, and tolerability in the context of other current FDA-approved topical therapies for CTCL.